Coaching Skills for Responding to Affect - Leigh Kibby (International Journal of Evidence Based Coaching and Mentoring, 2007)
Affective-cognitive integration is a crucial skill for human development and therefore must also be a key enabler in coaching. This paper proposes coaching techniques that facilitate affective-cognitive integration in the light of theory related to emotions triggering. It also explores how emotional sharing, through language, enables an interaction between affect and cognition that assists the integration of both and therefore can be utilized for coaches for enabling self-awareness and development.